Literature Study: Genetic Mutations in Antibacterial Resistance - Wahyuni, Riska (International Journal of Ecophysiology, 2025)
This study aims to understand how molecular and genetic mechanisms contribute to the development of antibacterial resistance and its impact on public health. The method used is a literature review by analyzing various books and scientific journals. Antibacterial resistance occurs when microorganisms become resistant to drugs that should effectively eliminate them, making treatment less effective. The misuse and overuse of antibiotics are the main causes of this issue. In Indonesia, easy access to antibiotics without a prescription worsens the situation. As a result, infections become more difficult to treat, prolonging illness and increasing the risk of death. Several bacteria, such as Pseudomonas aeruginosa, Escherichia coli, and Klebsiella pneumoniae, have shown high levels of resistance, particularly in hospitals. This resistance can develop through genetic mutations and the transfer of genetic material between bacteria. Therefore, antibacterial resistance is a serious threat that requires special attention in its control efforts.